2013
DOI: 10.5433/1679-0359.2013v34n1p455
|View full text |Cite
|
Sign up to set email alerts
|

Inversão sexual de alevinos de tilápias do Nilo (Oreochromis niloticus) variedade Supreme, submetidos a diferentes temperaturas durante fase de diferenciação sexual

Abstract: ResumoEste experimento avaliou os efeitos da temperatura na inversão sexual, sobrevivência e presença de deformidades em larvas de tilapia submetidas aos seguintes tratamentos controle (28ºC + ração 60 mg kg -1 de 17 α-metiltestosterona), 28, 30, 32 e 34ºC. Os resultados demonstraram diferença estatística entre a proporção de machos, sendo que as temperaturas controle, 32 e 34ºC (98; 91; 96 %, respectivamente) apresentaram resultados superiores aos obtidos para os tratamentos 28 e 30ºC (71 e 82 %). A sobrevivê… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
1
0
Order By: Relevance
“…Faster growth of males (Bardach, Ryther, & McLarney, 1972), positive anabolic effect of the hormone (Yamazaki, 1976), and activation of other endogenous anabolic hormones enhancing growth (Lone & Matty, 1980) are observed in hormone-treated fish, which promoted better performance compared to untreated fish. However, the effect of hormone in fish growth seems to be controversial; androgens may positively or negatively affect the health and growth of fish (Abo-Al-Ela, 2018; Lone & Matty, 1980;Zanoni, Leal, Caetano Filho, Oliveira, & Ribeiro, 2013). In this study, no adverse effect due to hormone use was observed in Nile tilapia.…”
Section: Period Of Mt Administrationmentioning
confidence: 56%
“…Faster growth of males (Bardach, Ryther, & McLarney, 1972), positive anabolic effect of the hormone (Yamazaki, 1976), and activation of other endogenous anabolic hormones enhancing growth (Lone & Matty, 1980) are observed in hormone-treated fish, which promoted better performance compared to untreated fish. However, the effect of hormone in fish growth seems to be controversial; androgens may positively or negatively affect the health and growth of fish (Abo-Al-Ela, 2018; Lone & Matty, 1980;Zanoni, Leal, Caetano Filho, Oliveira, & Ribeiro, 2013). In this study, no adverse effect due to hormone use was observed in Nile tilapia.…”
Section: Period Of Mt Administrationmentioning
confidence: 56%
“…However, despite these advantageous qualities, there are still challenges in the breeding process, such as parental care, high reproductive capacity, and early sexual maturation, which can lead to overpopulation in cultivation nurseries, competition for space and food, and reduced growth rates of individuals (Mendes and Carvalho, 2016;Zanoni et al, 2013). As a result, the production of male-only populations in tilapia fish farming has become a common practice.…”
Section: Introductionmentioning
confidence: 99%
“…In aquaculture, the production of monosex batches of sh is carried out to explore characteristics associated with the phenotypic sex with the commercial interest, which provides higher pro tability (Reis et al 2016). Usually, single-sex batches for sh farming are obtained by applying sex inversion techniques directly through temperature manipulation (Zanoni et al 2013) The undifferentiated phase in gonad development, known as the labile period, is the period in which the gonads are most sensitive to the action of exogenous steroids (Park et al 2004). During this period the gonads start to develop, and the primordial germ cells can transform into oogonia or spermatogonia, depending on the hormone used.…”
Section: Introductionmentioning
confidence: 99%